CHEMICAL CHARACTERISTICS OF EEL FLOUR (MONOPTERUS ALBUS) WITH DIFFERENT DRYING METHODS - Ade Olga Dinayah June; Edison Edison; mery sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractEel is one type of fish that can be used because it has a high nutritional content. Eel can be used as raw material for fish meal because it is known to contain complete protein and amino acids. This study aims to determine the chemical composition of eel flour which is dried in the sun and oven. The research method used was an experiment by making eel flour dried in an oven and in the sun. Parameter analysis of chemical composition and calcium content. The results showed that using a drying oven using a light oven produced moisture (9.35%), ash (3.80%), protein (81.01%), fat (2.07%), calcium (2.66%). Eel flour was dried in the sun compared to using the sun with moisture, ash, protein, fat content, 9.99, 77. 60, 2.07%, and calcium content of 2.66%. The results showed that the eel flour which was dried in the sun and oven had different chemical compositions. Oven-dried flour is better than sun-dried flour.Key word: Chemical composition, calcium, dried method